KAJIAN TERHADAP BASYARNAS DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH - Fadzila Ulfa Nadia Ulfa Nadia (Universitas Janabadra, 2019)
The rapid development of the business world in the era of globalization resulted in increased disputes between business people. Efforts to resolve the dispute can be done through two ways, namely litigation and non-litigation. The Sharia banking law also stipulates that the settlement of disputes between banks and customers can be resolved in litigation and non litigation. Non litigation can use the Sharia Arbitration model which in Indonesia is run by BASYARNAS. This paper will discuss how is the position and authority of Sharia Arbitration as a settlement institution for Islamic banking disputes and how are the obstacles in the implementation of sharia arbitration in Indonesia. This study uses normative legal research methods, with the aim to solve legal issues and provide a description of what is supposed to be prescription. The results of the discussion show that Sharia Arbitration in resolving Islamic banking disputes is institutionally carried out by BASYARNAS by using sharia principles that are constitutionally based on Article 29 of the 1945 Constitution of the Republic of Indonesia and the principle of freedom of contracting Article 1338 of the Civil Code can be implemented and not contrary to positive law in Indonesia. Constraints in the implementation of sharia arbitration, especially in terms of the execution / execution of the decision because it must be appealed to the Chairperson of the local District Court with the possibility of being rejected if considered by the judge to violate the provisions of UUAAPS.